Reverse shoulder arthroplasty in revision surgery—Indications and results - Patricia Bergert; Ralf Henkelmann; Pierre Hepp; Jan Theopold (PLoS ONE, 2025)
Background The number of reverse shoulder arthroplasty (RSA) procedures performed worldwide has increased over the last 10 years, with a corresponding increase in revision shoulder arthroplasty (SRSA). SRSA is often used for post-traumatic revision surgery in cases of infections and failure of anatomical prostheses. Data on outcomes with specific detail for each indication for the prosthetic solution as a secondary treatment are scarce, and inhomogeneous. Methods The questionnaires were sent by mail to 65 patients who underwent SRSA between January 2014 and November 2023. Based on the indications for SRSA, patients were categorized into post-traumatic shoulder arthritis, humeral head necrosis, failed proximal humerus fractures, failed proximal humerus osteosynthesis, prostheses loosening, and infection groups. Results Of the 65 patients included in the study, 39 completed the questionnaire, and the mean follow-up duration was 44 months (range, 12–104 months). The Constant score ranged from 28 points for all 6 groups (range, 38–66). The post-infection group showed the highest results, with 66 points (range, 24–90) on the Constant score; followed by 26 points (range, 49–6) points on the DASH score; and 0.90 (range, 0.763–1) on the EQ-5D-5L. Failed proximal humerus fractures presented the lowest scores: 38 points (range, 22–63) on the Constant score; 51 points (range, 73–30) points on the DASH score; and 0.61 (range, -0.496–1) on the EQ-5D-5L. Conclusions No previous study has investigated the influence of indications on the clinical outcome of SRSA so circumstantial. In this study, the highest outcome scores were observed in the post-infection group, whereas the lowest scores were observed in the failed humerus fracture group. Our results underline the influence of the indication on the clinical outcome of SRSA.